Number-conserving linear response study of low-velocity ion stopping in a collisional magnetized classical plasma - Nersisyan Hrachya B.; Deutsch Claude (EPJ Web of Conferences, 2013)
The low-velocity stopping power of ions in a magnetized collisional plasma is studied through the linear response theory. The collisions are taken into account through a number-conserving relaxation time approximation. One of the major objectives of this study is to compare and contrast our theoretical results with those obtained through a diffusion coefficient formulation based on Dufty-Berkovsky relation.